(untitled) (International Journal of Engineering and Computer Science, 2016)
Nowadays the popularity of multimedia contents search is increasing rapidly such as images, videos, and the audio. Among them, the images are much popular for search and data retrieval processes. In literature there are a number of techniques are exist for efficient and precise image retrieval but according to the conclusion of literature the content based techniques are a much promising approach. In content-based image retrieval systems, the image internal descriptors or features are used for representing the image contents. In these descriptors the shape, colour and texture are primary image content descriptors. A number of works are available for different combinations of these features but there is work exist for the texture analysis. In order to recognize the feature based similar objects, the texture feature played an essential role.